Orchestration of Adaptive T Cell Responses by Neutrophil Granule Contents - Danielle Minns; Katie Jane Smith; Emily Gwyer Findlay (Mediators of Inflammation)
Neutrophils are the most abundant leukocytes in peripheral blood and respond rapidly to danger, infiltrating tissues within minutes of infectious or sterile injury. Neutrophils were long thought of as simple killers, but now we recognise them as responsive cells able to adapt to inflammation and orchestrate subsequent events with some sophistication. Here, we discuss how these rapid responders release mediators which influence later adaptive T cell immunity through influences on DC priming and directly on the T cells themselves. We consider how the release of granule contents by neutrophils—through NETosis or degranulation—is one way in which the innate immune system directs the phenotype of the adaptive immune response.